Assess The Awareness Level Among Makkah Hospitals Regarding Occurrence Variance Reporting (The Review of Diabetic Studies, 2025)
AimsThis study aims to evaluate staff awareness of occurrence variance reporting (OVR) in Makkah hospitals, with a focus on patient safety incident reporting. The objective is to identify the types and frequencies of reported events, analyze the consistency of reporting over time, and examine the primary methods used to disseminate lessons learned to improve patient safety practices.MethodsA retrospective study was conducted over three years (2021-2023) across 10 governmental hospitals in Makkah, using OVR data categorized by incident type and severity. Data analysis was performed using Microsoft Excel to calculate frequencies, trends, and patterns across different incident categories and time periods. Reporting methods, such as alerts, meetings, and presentations, were also examined for their effectiveness in enhancing staff awareness.FindingsThe total number of OVRs decreased annually, from 33,170 in 2021 to 24,423 in 2022, and then to 22,201 in 2023. Medication errors, patient care management, documentation issues, staff-related concerns, and laboratory-related issues were consistently the most frequently reported categories. The most effective methods for disseminating lessons learned included alerts and presentations, which were used with varying frequency over the three-year period. Catastrophic incidents, although rare, have increased, highlighting areas for further improvement in patient safety practices.ConclusionThe decline in reported incidents suggests potential improvements in hospital practices or changes in reporting behavior, possibly due to fear of repercussions. To sustain improvements, it is recommended to enhance communication strategies and foster a supportive reporting environment, encouraging all staff to actively participate in patient safety initiatives.